QRS Complex Detection on Heart Rate Variability Reading Using Discrete Wavelet Transform - Arga Wihantara; I Dewa Gede Hari Wisana; Andjar Pudji; Sari Luthfiyah; Vijay Anant Athavale (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
Heart Rate Variability or heart rate in humans is used to monitor the function of the human heart. This research designed a tool to compare the results of heart rate readings using the discrete wavelet transform method to facilitate the detection of R peak. This can be obtained by evaluating and studying each decomposition result from level 1 to level 4 on Discrete Wavelet Transform processing using Haar mother wavelets. This study further used a raspberry pi 3B as the microcontroller of the data processor obtained from the ECG module. Based on the results obtained in this study, it can be concluded that in heart rate readings, level 2 decomposition details coefficient had the best value as data processing that helps the heart rate readings with an error value of 0.531% compared to HRV readings that obtained 0.005 using phantom tools and a standard deviation of 0.039. Furthermore, the advantage obtained from this tool is a good precision value in HRV and BPM readings. In reading the HRV of the respondent, it was found that each initial condition of the patient's HRV would be high due to the respondent's unstable condition. The disadvantage of this tool is a delay in running the program and no display in the form of a signal in real time.